Oxygen isotope variability in conodonts: implications for reconstructing Palaeozoic palaeoclimates and palaeoceanography - Wheeley, JR; Smith, M; Boomer, I (2012)
Conodonts have the potential to elucidate the intricacies of Palaeozoic climates, especially if δ 18O values of single apatitic tooth-like 'elements' can be used to map evolving sea surface temperatures and differentiate oceanic water masses. Their ecological distribution as pelagic and nektobenthic organisms, high-resolution biostratigraphy, and abundance in Cambrian-Triassic rocks qualifies them as potentially robust climate archives. Previous ion microprobe conodont δ 18O studies have proceeded directly to palaeotempera-ture interpretation without appreciation of inter- and intra-element variability or post-mortem artefacts. Here, ion microprobe analyses of Ordovician and Silurian conodonts establishes that: intra-element crown tissue δ 18O typically varies by <1%o (53% of conodonts analysed), is normally <2%o (92% of analyses), and rarely varies by 2-4%o; δ 18O can vary across elements, suggesting a microstructural and/or diagenetic control; δ 18O can vary between species representatives by c. 3%o; δ 18O of pelagic and nektobenthic taxa can be offset by 2-3%o; elements processed with formic acid have highly variable δ 18O; and thermal alteration does affect δ 18O. Conodont ion microprobe δ 18O values are comparable with those of bulk methods, but utilization of material with no consideration of geological context or processing history may introduce significant artefacts. A protocol for future conodont oxygen isotope ion microprobe studies is proposed.